2013
DOI: 10.1109/jdt.2012.2230395
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Light Output Power and Growth Mechanism of GaN-Based Light-Emitting Diodes Grown on Cone-Shaped ${\hbox{SiO}}_{2}$ Patterned Template

Abstract: In this study, we successfully transferred the patterns of a cone-shaped patterned sapphire substrate (CPSS) into SiO layer to fabricate a cone-shaped SiO patterned template by using nanoimprint lithography (NIL). The GaN-based light-emitting diodes (LEDs) were grown on this template by metal-organic chemical vapor deposition (MOCVD). The transmission electron microscopy (TEM) images suggest that the stacking faults formed near the cone-shaped SiO patterns during the epitaxial lateral overgrowth (ELOG) can eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Such a result is in good agreement with the published results reported by other research groups. 21,[33][34][35][36][37] It is clear that there is a broad range with fewer dislocations above Area D. Chiu et al and Chen et al have reported that stacking faults can block threading dislocations effectively, 38,39) which is the reason why fewer threading dislocations occur above the patterns. More detailed study of the formation of stacking faults in the PSS case has been performed.…”
Section: Resultsmentioning
confidence: 99%
“…Such a result is in good agreement with the published results reported by other research groups. 21,[33][34][35][36][37] It is clear that there is a broad range with fewer dislocations above Area D. Chiu et al and Chen et al have reported that stacking faults can block threading dislocations effectively, 38,39) which is the reason why fewer threading dislocations occur above the patterns. More detailed study of the formation of stacking faults in the PSS case has been performed.…”
Section: Resultsmentioning
confidence: 99%
“…The cone-shaped PSS is widely used for the elaboration of GaN-based blue and green LED applications, while ultra-violet LED applications mostly use pit-shaped PSS [ 15 , 16 ]. By replacing the material in the cones with silicon oxide ( n = 1.45), the LEE can be further enhanced as it becomes harder for the light to penetrate through the substrate [ 17 ]. The LEE promotion is achieved with the total reflection enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…14,15) Various PSS parameters with different pitch, shape and height are utilized to grow LED structures in order to obtain the best device performance. [16][17][18] The compressive strain and TD density could be effectively reduced with suitable pattern-designed PSSs. 17) Spatially resolved micro-Raman spectroscopy has recently been used to observe the in-plane strain distribution by measuring the E 2 (high) Raman peak variation in the GaN epilayer grown on the top of the plane or cone areas of the PSS.…”
Section: Introductionmentioning
confidence: 99%